2008
DOI: 10.1590/s1516-35982008000900001
|View full text |Cite
|
Sign up to set email alerts
|

Exigência de fósforo disponível para juvenis de tilápia-do-nilo

Abstract: RESUMO -Determinou-se a exigência de fósforo disponível para juvenis de tilápia-do-nilo. Utilizou-se delineamento em blocos inteiramente casualisados com quatro tratamentos e quatro repetições. Foram fornecidas manualmente, durante 120 dias, dietas com 32% de proteína bruta e 3.050 kcal de energia digestível/kg, suplementadas com fosfato bicálcico de forma a se obterem 0,21; 0,40; 0,56 e 0,71% de fósforo disponível. Não houve efeito dos níveis de fósforo da dieta sobre o consumo, os teores de proteína e extrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
3
5
0
6
Order By: Relevance
“…Residual phosphorus presented a linear effect and increased based on phosphorus inclusion levels. Similar data were observed by Furuya et al (2008), who studied the availability of this mineral for tilapia and indicated that the excretion of fecal phosphorus per kg of produced fish increased linearly with available phosphorus levels of 0.25, 0.35, 0.45 and 0.55%. The data from the present study are also in accordance with Oliva-Teles and Pimentel-Rodrigues (2004), which shows that diets with available phosphorus values above the requirements for pacu (0.4% to 0.6% according to Signor et al (2011) andDiemer et al (2014), respectively) are not required.…”
Section: Resultssupporting
confidence: 83%
“…Residual phosphorus presented a linear effect and increased based on phosphorus inclusion levels. Similar data were observed by Furuya et al (2008), who studied the availability of this mineral for tilapia and indicated that the excretion of fecal phosphorus per kg of produced fish increased linearly with available phosphorus levels of 0.25, 0.35, 0.45 and 0.55%. The data from the present study are also in accordance with Oliva-Teles and Pimentel-Rodrigues (2004), which shows that diets with available phosphorus values above the requirements for pacu (0.4% to 0.6% according to Signor et al (2011) andDiemer et al (2014), respectively) are not required.…”
Section: Resultssupporting
confidence: 83%
“…Ao avaliar a exigência de fósforo disponível para juvenis de tilápia-do-nilo, Furuya et al (2008b) observaram valores de proteína de 18,18% e de lipídios na carcaça de 3,46%, que são superiores e inferiores, respectivamente, aos observados no presente trabalho. Hernández et al (2010), em estudo sobre a substituição de farinha de peixe por farinhas de suínos e aves, para alevinos de tilápia-do-nilo, verificaram teores de proteína de 18,6% e de lipídios de 6,3%, para peixes alimentados com dieta contendo farinha de peixe.…”
Section: Resultsunclassified
“…Os baixos valores de fósforo exigidos para o pacu podem ser atribuídos ao hábito alimentar onívoro da espécie (Souza et al, 2003). O desempenho produtivo da maioria dos peixes é influenciado pelo nível de fósforo (Miranda et al, 2000;Ribeiro et al, 2006;Furuya et al, 2008a;Furuya et al, 2008b), comprovando que o desempenho depende de dieta balanceada em fósforo. As porcentagens recomendadas para os peixes variam de acordo com a espécie, conforme relatado por Boscolo et al (2005) A necessidade de fósforo em peixes depende, entre outros fatores, da constituição do trato digestório e da fonte de fósforo (Steffens, 1987).…”
Section: Resultsunclassified